The Ideal Concept of Integrated-Based Ngrenehan Coastal Management for Community Welfare (Integrated Coastal Zone Management Approach) - Berliant Pratiwi; Sunarno Sunarno; Izzy Al Kautsar (Universitas Muhammadiyah Purwokerto, 2022)
This study examines the ideal concept of integrated-based coastal area management for community welfare. This study aims to analyze the management of coastal areas at Ngrenehan Beach and describe the ideal concept of managing coastal areas at Ngrenehan Beach with an ICZM approach in the future. This study uses a legal, social research method with a conceptual approach. The results of this study are (1) the Kanigoro village government provides solutions in the form of public policies that reflect the integrated management of coastal areas based on the tourism economy, community empowerment, and a sustainable environment; (2) elements of human resources, village infrastructure, and stakeholder communication are still problems that need solutions related to optimizing their implementation. These three elements are the principal basis of an integrated-based management pyramid. If these elements have not been implemented optimally, it is feared that the process of village development and development to become an empowered and civilized village will be hampered.